A novel method for non-linear design of CLT wall systems. (15th July 2018) - Tamagnone, G.; Rinaldin, G.; Fragiacomo, M.
Highlights: Simplified method for the seismic design of connections at the base of a CLT wall system. Assess of the most probable failure mechanism of a CLT wall system for a given set of external loads. Information on the rocking capacity of a CLT wall system. Evaluation of a bending moment-axial force resistant domain for a CLT wall system. Abstract: In this paper, a non-linear procedure for the seismic design of metal connections in cross-laminated timber (CLT) walls subjected to bending and axial force is presented. Timber is conservatively modelled as an elasto-brittle material, whereas metal connections (hold-downs and angle brackets) are modelled with an elasto-plastic behavior. The reaction force in each connection is iteratively calculated by varying the position of the neutral axis at the base of the wall using a simple algorithm that was implemented first in a purposely developed spreadsheet, and then into a purposely developed software. This method is based on the evaluation of five different failure mechanisms at ultimate limit state, starting from the fully tensioned wall to the fully compressed one, similarly to reinforced concrete (RC) section design. By setting the mechanical properties of timber and metal connections and the geometry of the CLT panel, the algorithm calculates, for every axial load value, the ultimate resisting moment of the entire wall and the position of the neutral axis. The procedure mainly applies to platform-type structures with hold-downs and angle brackets connections at the base of the wall and rocking mechanism as the prevalent way of dissipation. This method allows the designer to have information on the rocking capacity of the system and on the failure mechanism for a given distribution of external loads. The proposed method was validated on the results of FE analyses using SAP2000 and ABAQUS showing acceptable accuracy.